2022
DOI: 10.3389/fcell.2022.876815
|View full text |Cite
|
Sign up to set email alerts
|

The Intimate Connection Between Lipids and Hedgehog Signaling

Abstract: Hedgehog (HH) signaling is an intercellular communication pathway involved in directing the development and homeostasis of metazoans. HH signaling depends on lipids that covalently modify HH proteins and participate in signal transduction downstream. In many animals, the HH pathway requires the primary cilium, an organelle with a specialized protein and lipid composition. Here, we review the intimate connection between HH signaling and lipids. We highlight how lipids in the primary cilium can create a speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 180 publications
0
7
0
Order By: Relevance
“…Despite clustering with the single-treatment groups in our PCA analysis, the enrichment pro le was quite different, relating primarily to lipids. Lipids play multiple key roles in hedgehog signaling, including as ligands and as covalent modi ers of effector molecules [21,22]. The role of lipids in Gata3-mediated developmental processes is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clustering with the single-treatment groups in our PCA analysis, the enrichment pro le was quite different, relating primarily to lipids. Lipids play multiple key roles in hedgehog signaling, including as ligands and as covalent modi ers of effector molecules [21,22]. The role of lipids in Gata3-mediated developmental processes is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic of plasma membrane proteins and lipids in and out of cilia is controlled by a diffusion barrier in which PI4P (which is the predominant phosphoinositide in the ciliary shaft) and PI(4,5)P 2 (which is the predominant phosphoinositide the ciliary pocket) play an important role (Chavez et al 2015, Garcia-Gonzalo et al 2015, Nguyen et al 2022, Ojeda Naharros and Nachury 2022). Impairment of SJ1 function may disrupt the function of the diffusion barrier between the two compartments by perturbing the physiological concentration and relative ratio of PI4P and PI(4,5)P 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, or in addition, SJ1 may help control membrane protein clearing from cilia indirectly via its function in the endocytic pathway (Cremona et al 1999) as the fate of ubiquitinated proteins is to undergo endocytosis in the ciliary pocket for subsequent targeting to degradation (Nachury and Mick 2019, Shinde et al 2020). While SJ1 appears to have a primary role in the shedding of endocytic factors after endocytosis (Nguyen et al 2022), its loss-of-function, as shown by studies of nerve terminals, also results in a back-up of endocytic traffic with a partial stranding in the plasma membrane of proteins and membrane that needs to be internalized. As we have now shown that a pool of SJ1 is concentrated at the ciliary base, a special role of this protein in the endocytosis that occurs at the ciliary pocket is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Different PI species bind different pleckstrin-homology (PH) domain-containing effectors and determine their subcellular localization, e.g., in the cilium (Chavez et al, 2015;Garcia-Gonzalo et al, 2015). Furthermore, other lipids, e.g., sterols, have been shown to fine tune ciliary signaling, such as Hh signaling, as reviewed by others (Nguyen et al, 2022).…”
Section: Compositional Dynamicsmentioning
confidence: 99%